Making the case for supporting broad energy efficiency programmes: Impacts on household incomes and other economic benefits. (December 2017) - Figus, Gioele; Turner, Karen; McGregor, Peter; Katris, Antonios
Abstract: In recent years, an overly narrow focus on rebound effects has limited the extent of researcher and policy attention afforded to the wider multiple benefits of increased energy efficiency. Our objective is to focus policy attention on the sustained added value to the economy that is created by improving energy efficiency in the residential sector. Governments around the world are committed to increasing energy efficiency more generally, but often focus public support in low income households where energy poverty is a particular concern. However, governments operate in a context of multiple objectives where energy efficiency is expected to deliver significant reductions in carbon emissions alongside sustainable economic development. We use a UK CGE model to consider the general effects of supporting increases in energy efficiency in residential energy use. Our results demonstrate that the increase in GDP, and economic activity more generally, triggered by increased energy efficiency delivers more in terms of increased household incomes than the efficiency improvement itself. We find that the more wide ranging the boost to energy efficiency, the greater the economic expansion and associated returns are likely to be, and the less the means of financing through public budgets will erode the benefits over time. Highlights: Expansionary impacts of increased energy efficiency boost household incomes. Benefits to low income households are enhanced by wider energy efficiency increases. Benefits via wage income may be limited in low income relative to other households. There is a wider economic payback to public support of energy efficiency. Greater expansion limits the negative impacts of any funding requirement.